Clarification of the type series of Amphibolurus barbatus microlepidotus Glauert, 1952 (= Pogona microlepidota) (Reptilia: Squamata: Agamidae) - Ellis, Ryan J. (Zootaxa, 2018)
Ludwig Glauert (1952, p. 168) established the name Amphibolurus barbatus microlepidotus (= Pogona microlepidota) for a new agamid species (family Agamidae) from the type locality of “Drysdale River Mission, North Kimberley”, Western Australia and listed two specimens of the Western Australian Museum (WAM) collected by “Rev. Father [Raymundus] Salinas” in July 1922 as “types”. The two registrations forming the type series presented by Glauert were WAM R591 and WAM R592, which in accordance with Article 72.1.1. of the International Code for Zoological Nomenclature (the Code; International Commission on Zoological Nomenclature 1999) are considered syntypes. The two registrations presented by Glauert in the original publication (WAM R591–592) are in error, both registrations are associated with specimens of other species not matching the description or collection data presented by Glauert in the original description of A. b. microlepidotus. The specimen associated with WAM R591 is a Pseudonaja affinis Günther, 1872 (Serpentes: Elapidae), collected by M. Sweeting from the suburb of Leederville in Perth, Western Australia and WAM R592 a specimen of Neelaps calonotus (Duméril, Bibron, & Duméril, 1854) (Serpentes: Elapidae) collected by C. Thomas from the Perth suburb of West Guildford (now Bassendean), Western Australia (Fig. 1). The P. affinis specimen (WAM R591) is purportedly a whole specimen stored in a 75% ethanol solution; however, extensive searches failed to locate the specimen in the WAM collection and it is presumed lost or disposed of. In the early half of the 20th century, large and easily identifiable specimens were sometimes disposed following identification, registration and collection of morphological data due to their preservation and storage difficulty (see Smith 1981). The N. calonotus specimen (WAM R592) is now an alizarin-stained body in a glycol solution with skin stored separately in 75% ethanol (Fig. 1). The erroneous registration numbers provided by Glauert technically placed the name A. b. microlepidotus into synonymy with either N. calonotus or P. affinis depending on lectotype selection.